Faktor-faktor yang mempengaruhi kepuasan kerja dan kinerja karyawan bank muamalat cabang samarinda - Syaharuddin Syaharuddin (Faculty of Economics and Business Mulawarman University, 2016)
This study was conducted in its capital Samarinda branch to specifically examine leadership work environment and organizational commitment to employee satisfaction and employee performance The purpose of this study was to determine the effect of leadership, working environment and the organization's commitment to performance, either direct or indirect influence through employee satisfaction. Variables used in this study are leadership, work environment, oranigasi commitment, job satisfaction, and employee performance. The method used to analyze the data of this study is the Path Analysis (path analysis). The sample used in this study as many as 95 samples of all employees of the bank Muamalat branch Samarinda.Keywords: leadership, work environment, organizational commitment, job satisfaction and performance